Mechanistic Insights Into the Anticancer Properties of the Auranofin Analog Au(PEt3)I: A Theoretical and Experimental Study - Tolbatov, Iogann; Cirri, Damiano; Marchetti, Lorella; Marrone, Alessandro; Coletti, Cecilia; Re, Nazzareno; La Mendola, Diego; Messori, Luigi; Marzo, Tiziano; Gabbiani, Chiara; Pratesi, Alessandro (Frontiers in Chemistry, 2020)
Au(PEt3)I (AF-I hereafter), the iodide analogue of the FDA-approved drug auranofin (AF hereafter), is a promising anticancer agent that produces its pharmacological effects through interaction with non-genomic targets such as the thioredoxin reductase system. AF-I is endowed with a very favorable biochemical profile showing potent in vitro cytotoxic activity against several cancer types including ovarian and colorectal. Remarkably, in a recent publication, some of us reported that AF-I induces an almost complete and rapid remission in an orthotopic in vivo mouse model of ovarian cancer. The cytotoxic potency does not bring about highly severe side effects making AF-I very well tolerated even for higher doses than the pharmacologically active ones. All these promising features led us to expand our studies on the mechanistic aspects underlying the antitumor activity of AF-I. We report here on an integrated experimental and theoretical study on the reactivity of AF-I, in comparison with auranofin, toward relevant aminoacidic residues or their molecular models. Results point out that the replacement of the thiosugar moiety with iodide affects significantly the overall reactivity toward the amino acid residues histidine, cysteine, methionine and selenocysteine. Altogether, the obtained results contribute to shed light into the enhanced antitumoral activity of AF-I compared with AF.